1978
DOI: 10.3109/00365517809102434
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte-Zn-protoporphyrin as an indicator of lead exposure

Abstract: Measurement of erythrocte-Zn-protoporphyrin with a haematofluorimeter on blood samples from eighty-four lead-exposed individuals has been compared with a fluorimetric determination of the extracted porphyrins. The results agreed well, and the interference from bilirubin and unchelated protoporphyrin was low. An exponential increase in erythrocyte protoporphyrin and a linear decrease in blood haemoglobin with increased blood lead was found in seventy-nine males with occupational lead exposure. The haematofluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…In the exposed population, however, 15 workers showed one or more results in excess Exposed group Table 2. Results of exposure tests of the lead-exposed group of the permissible levels, i.e., 2.9 ,umol Pbll blood, 350 }lmol ZPP/mol Hb (Fe), or 500 ,umol Pblkg hair (11,12,30). The median exposure levels were only moderately increased (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the exposed population, however, 15 workers showed one or more results in excess Exposed group Table 2. Results of exposure tests of the lead-exposed group of the permissible levels, i.e., 2.9 ,umol Pbll blood, 350 }lmol ZPP/mol Hb (Fe), or 500 ,umol Pblkg hair (11,12,30). The median exposure levels were only moderately increased (table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The amount of lead in the blood, however, is not hazardous itself, but it may be used as a predictor of toxic effects such as anemia or intellectual impairment. It has recently been shown that ZPP correlates better than PbB with hemoglobin concentrations in the blood (12,16). Thus, ZPP may be a better predictor for anemia than PbB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these characteristics, the presence of ZPP has been utilized as a marker to chronic lead absorption in several studies [4][5][6] . ZPP represents the average effect of lead absorption during 3~4 months 7,8) . Several investigators reported a positive correlation between concentrations of blood lead and ZPP when workers were exposed to high level of lead [3][4][5][6][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%